Macrophages in ventricular remodeling and heart failure: orchestrators of inflammation and repair - Feng, Han; Hu, Wenhui; Liu, Ying; Xu, Xiaoshuang; Zhou, Ping; Qu, Chen; Liu, Zhengxia (Frontiers in Immunology, 2025)
Heart failure is a complex clinical syndrome caused by structural and/or functional cardiac abnormalities. Ventricular remodeling contributes to its progression. Cardiac macrophages regulate inflammation, fibrosis, and tissue repair that drive this process. In this Review, we describe the origins and phenotypic diversity of cardiac macrophages, including both resident and monocyte-derived subsets. In the left ventricle, macrophages respond to ischemia, pressure overload, and metabolic stress. In the right ventricle, they display distinct immune features under pulmonary hypertension and other stress conditions. We further discuss the interactions between macrophages and other cardiac cell types, such as fibroblasts, cardiomyocytes, endothelial cells, and lymphocytes. These interactions shape the immune environment and structural integrity of the myocardium. We also highlight recent advances in single-cell and spatial technologies that reveal chamber-specific macrophage signatures. Finally, we summarize emerging therapeutic strategies targeting macrophages, including pharmacological agents, engineered cell therapies, and nanoparticle-based delivery systems. Together, these insights provide a framework for understanding macrophage-mediated remodeling and for guiding precision immunotherapies in heart failure.